Research Integrity : Dishonesty and Research Misconduct within the Medical Profession - Amir, Haeril (PT.Mantaya Idea Batara, 2025)
Research Integrity is a moral and ethical principle in research. Research Integrity is often associated with the process until the publication of research reports in journals or databases. Research integrity is also related to the honesty of a researcher in obtaining research data, processing research data, and the publication process until the application of research results. Enforcement of research integrity as an effort to maintain the quality and integrity of researchers to restore the true purpose of research and the research results will have an impact on the development of technology and the advancement of human resources and other goals.